2009
DOI: 10.1007/s10705-009-9286-3
|View full text |Cite
|
Sign up to set email alerts
|

Differential retention of carbon, nitrogen and phosphorus in grassland soil profiles with long-term manure application

Abstract: Liquid hog manure (LHM) is a valuable source of nutrients for farm production. Long-term experimental plots that had received LHM applications of 0, 50, and 100 m 3 ha -1 annually for 20 years were analyzed for total soil C, N and P storage. Applications increased total soil N and P by 1,200 kg N ha -1 and 850 kg P ha -1 at 100 m -3 LHM year -1 , compared to the control treatment. However, C storage did not increase with LHM rates and was lower in the 50 m 3 ha -1 LHM treatment (86 Mg C ha -1 ) than in the 0 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
2
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(38 citation statements)
references
References 17 publications
3
31
2
2
Order By: Relevance
“…Such increasing N release after regular application of organic fertilizers with high proportions of organic N has been reported by Gutser et al (2005). Residual effects expressed as an increase in plant N uptake from N org after long-term application of animal slurry are well described (Martynuik et al, 2002;Schröder et al, 2005;Angers et al, 2010) and are often associated with an observed increase in soil N t . However, the increase in the AANU from the first to the fifth fertilizer application differed among the organic fertilizers with all biogas residues from cofermentation (CF1 to CF4) being significantly lower compared to the plant-based residue PB3 and cattle slurry in both soils and PB2 in the Dürnast soil.…”
Section: Discussionmentioning
confidence: 72%
“…Such increasing N release after regular application of organic fertilizers with high proportions of organic N has been reported by Gutser et al (2005). Residual effects expressed as an increase in plant N uptake from N org after long-term application of animal slurry are well described (Martynuik et al, 2002;Schröder et al, 2005;Angers et al, 2010) and are often associated with an observed increase in soil N t . However, the increase in the AANU from the first to the fifth fertilizer application differed among the organic fertilizers with all biogas residues from cofermentation (CF1 to CF4) being significantly lower compared to the plant-based residue PB3 and cattle slurry in both soils and PB2 in the Dürnast soil.…”
Section: Discussionmentioning
confidence: 72%
“…The soil was an imperfectly drained Le Bras series, silty clay loam (270 g clay kg − 1 , 420 g silt kg − 1 ; loamy, mixed, frigid, Typic Humaquept). Details of soil characteristics and site history can be found in Angers et al (2010) and MacDonald et al (2010;2011).…”
Section: Study Site and Experimental Designmentioning
confidence: 99%
“…Another issue is the potential effect of increasing fresh organic carbon supply to the soil (plant exudates and residues, organic amendment) on the mineralization of "old" soil organic carbon, the so-called "priming effect" (Fontaine et al 2007). While solid manure has been observed to promote carbon sequestration in soils, liquid manure, which contains highly decomposable carbon, may lead to a large priming effect at intermediate application rates (Angers et al 2010). In addition, questions rise on the link between organic carbon and nitrogen in soils and the effect of either carbon or nitrogen loss or gain on the coupled system.…”
Section: Introductionmentioning
confidence: 99%